BEHAVIOR OF THE NGUYEN DYNASTY FOR TEACHERS IN SOUTHERN VIETNAM - Thi Minh Hang Ngo (Tạp chí Khoa học Đại học Đà Lạt)
This article examines the educational policies and cultural behavior of the Nguyen Dynasty toward teachers in the South to answer the following questions: What were the policies for establishing schools in the South? What was the purpose of the Nguyen Dynasty in regulating teachers and students? What were the differences in behavior of the Nguyen Dynasty toward Southern teachers compared with other localities? What were the similarities and differences between public and private schools in the South? To answer these questions, we collect and document bibliographic sources. Using methods of comparison, analysis, and synthesis, we outline the process of implementing educational policies in general, policies to manage teachers in the South in particular, and assess the role of teachers and teacher standards in improving the quality of education during the Nguyen Dynasty. In addition, this article also compares the differences in the behavior of the Nguyen Dynasty toward teachers in public and private schools in different localities and provides comments and assessments on the cultural behavior of the Nguyen Dynasty toward teachers in the feudal South.